2009
DOI: 10.1021/bi901571t
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical Analyses of Synthetic Amyloid-β(1−42) Aggregates before and after Covalent Cross-Linking. Implications for Deducing the Structure of Endogenous Amyloid-β Oligomers

Abstract: A neuropathological hallmark of Alzheimer's disease (AD) is the presence of large numbers of senile plaques in the brain. These deposits are rich in fibrils that are composed of 40- and 42-residue amyloid-beta (Abeta) peptides. Several lines of evidence indicate that soluble Abeta aggregates as well as fibrils are important in the etiology of AD. Low levels of endogenous soluble Abeta aggregates make them difficult to characterize, but several species in extracts of AD brains have been detected by gel electrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 54 publications
(238 reference statements)
1
63
0
Order By: Relevance
“…This hypothesis has been challenged by the observation of Bitan et al [18] that SDS itself can artificially induce oligomerization. Other groups have confirmed this conclusion [19], [20], but it was also found that such artificial forms become disaggregated upon boiling in 1% SDS. Also, it is known that species resolved by SDS-PAGE differed markedly in terms of size and stability depending on the source of the oligomer: endogenous or synthetic [19], AD-derived or extracted material from transgenic mouse AD models [21].…”
Section: Introductionmentioning
confidence: 56%
“…This hypothesis has been challenged by the observation of Bitan et al [18] that SDS itself can artificially induce oligomerization. Other groups have confirmed this conclusion [19], [20], but it was also found that such artificial forms become disaggregated upon boiling in 1% SDS. Also, it is known that species resolved by SDS-PAGE differed markedly in terms of size and stability depending on the source of the oligomer: endogenous or synthetic [19], AD-derived or extracted material from transgenic mouse AD models [21].…”
Section: Introductionmentioning
confidence: 56%
“…Depending on the stoichiometry, Cu 2þ -Ab interactions can cause synthetic Ab to aggregate in vitro principally via an oligomer-forming pathway or a fibrillogenic pathway (Brzyska et al 2009;Moore et al 2009;Olofsson et al 2009a;Tõugu et al 2009;Haeffner et al 2010). That is, at subequimolar Cu 2þ :Ab ratios, amyloid fibrils form; at supra-equimolar ratios, stable oligomers form first, then dityrosine cross-linkages occur (Smith et al 2007).…”
Section: Ab and Coppermentioning
confidence: 99%
“…Cu 2þ as a redox-active entity can also induce oxidative modification to Ab, particularly at Tyr10 with consequent dityrosine covalent cross-links (Drew et al 2009a,b;Moore et al 2009;Jiang et al 2010). Other residues, such as Met35, may participate (Barman et al 2009;Butterfield et al 2010), but this is not proven (da Silva et al 2009).…”
Section: Ab and Coppermentioning
confidence: 99%
“…MOAB-2 was developed in the LaDu laboratory and is a high-affinity antibody specific for A␤ that does not detect APP. For the oA␤ ELISA, MOAB-2 was used as a capture antibody and biotinylated MOAB-2 as a detection antibody based on a previous protocol (46). This ELISA pairing detects synthetic oA␤ preparations but not monomeric A␤ using preparations of oA␤ optimized for the original protocol (data not shown) (46).…”
Section: Elisasmentioning
confidence: 99%
“…For the oA␤ ELISA, MOAB-2 was used as a capture antibody and biotinylated MOAB-2 as a detection antibody based on a previous protocol (46). This ELISA pairing detects synthetic oA␤ preparations but not monomeric A␤ using preparations of oA␤ optimized for the original protocol (data not shown) (46). These oA␤ preparations were used as a standard for measuring soluble oA␤ levels in EFAD mice.…”
Section: Elisasmentioning
confidence: 99%